Gut Microbiota Response to Experimental Acute Cold Stress in Juvenile Yellowfin Tuna (Thunnus albacares) - Junhua Huang; Zhengyi Fu; Wei Yu; Bowen Hou; Jinhui Wu; Tao Zhang; Zhenhua Ma (Journal of Marine Science and Engineering)
Environmental temperature declines significantly impact the physiological processes of marine organisms, particularly under the cool La Nina conditions, challenging yellowfin tuna (Thunnus albacares) aquaculture. Low temperatures affect fish metabolism and immune functions and can alter the gut microbiota composition, influencing health and growth. This study investigates the impact of low temperatures on the gut microbiota of juvenile yellowfin tuna. Fish were divided into a Low Temperature (LT) group (24 °C), an Ultra Low Temperature (ULT) group (18 °C), and a Control group (CG) (30 °C), with evaluations at 0, 12, 24, and 36 h using α-diversity analysis and microbial species composition. Results indicated a significant increase in the Ace index for the ULT group after 36 h of cold stress (p < 0.05), with no significant changes in the Shannon index. A decline in Proteobacteria and increases in Verrucomicrobiota and Firmicutes were observed in both LT and ULT groups. Additionally, both LT and ULT groups showed a significant rise in the Ace index at 36 h (p < 0.05), with a significant decrease in the Shannon index in the ULT group at 24 h. Furthermore, Firmicutes significantly increased at 12 h in both temperature groups (p < 0.05). These findings highlight the potential role of the gut microbiome in adapting yellowfin tuna to cold environments and provide microbial insights into their physiological adaptations, laying a foundation for further research and practical applications in aquaculture under cold conditions.